The Persuasiveness of debate a quasi-experimental study on Sto. Nin?o National High School Grade 12 HUMSS students? perception of the 1972 Philippine Martial Law Years as the golden era - Porras, Rey Anthony A.
This study employed Petty and Cacioppo?s Elaboration Likelihood model to investigate the persuasiveness of debate, alongside other factors such as family background, demographics, and socio-civic participation on students? perception of martial law as ?the golden era.? A pretest-posttest control group quasi-experimental design was used, wherein both treatment and control groups underwent tests before and after receiving the intervention, referred to as the pretest and posttest, respectively. The Wilcoxon Signed Rank Test was employed as the statistical tool to analyze the related samples. The results revealed key findings. First, significant differences were observed in the pretest and posttest scores of the treatment group, indicating a notable impact of the intervention. A significant difference was also found between the posttest of the treatment group and control group, suggesting that the persuasive elements employed in the intervention had an effect on participants? perception of martial law. The study also found that there were no significant differences between the control group's pretests and posttests and both groups' pretests. Proving that the control group had not changed after the experiment and that both experiments had been conducted under identical circumstances. Thus, the study concluded that the impact happened because of the debate as the study?s intervention, affirming the persuasiveness of debate on students? perception of martial law years as the country?s golden era. Furthermore, there were no other sources of information that were found to have a significant relationship with the persuasiveness of the debate. It follows that the perception they gained in the posttest is a result of the experiment and not by other factors. These findings contribute to our understanding of debate in influencing individuals? perception of martial law. The study highlights the importance of considering multiple mediums in shaping perceptions. These insights can inform communication strategies and media literacy programs aimed at fostering a nuanced understanding of our country?s pressing issues.